2020
DOI: 10.1016/j.healthpol.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Are frail elderly people in Europe high-need subjects? First evidence from the SPRINTT data

Abstract: Physical frailty and sarcopenia (PF&S) has received growing attention in empirical models of health care use. However, few articles focused on objective measures of PF&S to assess the extent of care consumption among the frail population at risk of dependency. Using baseline data from the SPRINTT study, a sample of 1,518 elderly people aged 70+ recruited in eleven European countries, we analyse the association between various PF&S measures and health care / long term care (LTC) use. Multiple health care and LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…Frailty is associated with old age and is characterized by increased vulnerability to stressors, placing older adults (OA) at high risk for adverse events such as falls, disability, hospitalization, institutionalization, and death (Cesari et al, 2016; Fried et al, 2001). In addition, frailty is associated with increased health care and long-term care (LTC) use (Roquebert et al, 2021; Sicsic et al, 2020). Frailty can be treated and reverted with exercise (Kojima et al, 2019), and there is increasing interest in diagnosing and treating frailty.…”
mentioning
confidence: 99%
“…Frailty is associated with old age and is characterized by increased vulnerability to stressors, placing older adults (OA) at high risk for adverse events such as falls, disability, hospitalization, institutionalization, and death (Cesari et al, 2016; Fried et al, 2001). In addition, frailty is associated with increased health care and long-term care (LTC) use (Roquebert et al, 2021; Sicsic et al, 2020). Frailty can be treated and reverted with exercise (Kojima et al, 2019), and there is increasing interest in diagnosing and treating frailty.…”
mentioning
confidence: 99%
“…Similarly, decreased cognitive function rose the risk for NCU (4,8,9,11,14). Using different assessment tools, previous studies (15,(17)(18)(19) consistently showed that physical frailty was associated with increased use of home care services. Based on Tilburg Frailty Indicator, Verver et al (18) observed that besides physical frailty, also the combination of physical, social (e.g., living alone, low social support), and psychological frailty (e.g., problems with memory) contributed to higher use of informal and home care.…”
Section: Introductionmentioning
confidence: 89%
“…As LTC is significantly associated with higher longevity, we consider the life expectancy at age 65 ( life_exp ). Besides, as longer life can be associated with an increase in the prevalence of chronic diseases [ 46 , 47 ], we also introduce two measures of frailty, the number of healthy life years at 65 (for men, healthylife_exp_M , and women healthylife_exp_F ) and the share of people aged over 65 with two or more chronic diseases ( cronic ).…”
Section: The Empirical Strategymentioning
confidence: 99%